Anteroposterior tibial translation during simulated isometric quadriceps contractions - Zavatsky, A; O'Connor, J (1995)
The anteroposterior tibial translations cause by simulated isometric quadriceps forces of up to 750 N were measured in vitro for two extension-restraining load placements at five flexion angles. Both quadriceps force and tibial translation were flexion-angle and load-placement dependent. Quadriceps force was linearly dependent on restraining force; tibial displacement was either very small (<1 mm) or increased non-linearly with increasing restraining force. The measured directions of tibial translation agreed with the predictions of a sagittal-plane knee model. From the displacement data, the directions and axes of tibial rotation were deduced. © 1995.